Estudo de melhoria no fluxo operacional do processo de beneficiamento de grãos em uma unidade armazenadora de grãos - Zanolla, Gabriel Augusto (2019)
The following study aims to improve the operational process of grain processing of a grain storage unit, since to meet market demands for higher quality and lower product cost, it is necessary to improve internal processes considering the best possible investment with a broad return. This requires the aid of tools contained in the lean methodology, to identify and eliminate operational bottlenecks. However, these tools require an extensive data collection to identify the cause or points of anomalies. The results of the application of this methodology indicated that two transport equipment were undersized compared to the operational capacity of the remaining components of the processing process. After performing the resizing calculation, it is concluded that some changes are necessary to reach the capacity of the rest of the process, and it is up to the company to accept or not the proposal to improve these equipment.